Early childhood female genital mutilation in Sierra Leone, 2008–2019 - Augustus Osborne; Camilla Bangura; Baindu Abu; Umaru Sesay (PLoS ONE, 2025)
Background Female genital mutilation remains a public health concern and human rights violation affecting young girls in Sierra Leone, despite global efforts to eliminate the practice. With its diverse socio-cultural background and varying regional practices, Sierra Leone presents a unique context for examining how female genital mutilation practices have evolved across different population subgroups. This study examined the early childhood female genital mutilation among women of reproductive age (15–49 years) who reported having FGM before the age of five in Sierra Leone. Methods The study utilised data from the Sierra Leone Demographic Health Survey rounds conducted in 2008, 2013, and 2019. The World Health Organisation Health Equity Assessment Toolkit software calculated various measures, including difference, ratio, population-attributable risk, and population-attributable fraction. An assessment was calculated for five stratifiers: age, education level, economic status, place of residence, and sub-national province. Results The prevalence of female genital mutilation among women of reproductive age (15–49 years) who reported undergoing the practice before the age of five in Sierra Leone declined from 23.2% in 2008 to 12.3% in 2019. By 2019, female genital mutilation showed minimal variation between women aged 40–49 and 15–19, as well as in urban-rural differences. Economic variations in female genital mutilation decreased but continued to disadvantage women in the poorest quintile. Educational variations in female genital mutilation decreased but still impacted women without formal education. Provincial variations in female genital mutilation widened, with the ratio between the Western and Northwestern provinces increasing from 1.8 in 2008 to 2.6 in 2019. Conclusion The results showed a decrease in early childhood female genital mutilationin Sierra Leone. While differences related to age groups and urban-rural residence have largely been eliminated, substantial differences persist across educational levels, economic status, and provinces. Most notably, the provincial differences between the Western and Northwestern provinces had widened, with the difference in ratio indicating that female genital mutilation practices remain disproportionately concentrated in some provincial areas. These results suggest that while national-level interventions have been partially successful, there is a critical need for targeted, context-specific approaches that address persistent socioeconomic and provincial variations to achieve a more equitable reduction in early childhood female genital mutilation across all population groups in Sierra Leone.